2017
DOI: 10.1186/s40405-017-0028-1
|View full text |Cite
|
Sign up to set email alerts
|

Family violence in a sample of treatment-seeking gamblers: the effect of having dependent children

Abstract: This study investigated the effect of problem gambler gender on the relationship between the gambler having dependent children (younger than 18 years) living at home and the gambler perpetrating or being a victim of family violence. The sample comprised 164 help-seeking gamblers (43% female; 37% with dependent child/ren) recruited from three national gambling treatment services in New Zealand. Family violence was measured using a modified version of the HITS scale covering physical, psychological, verbal, emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…However, by using gambling venues as safe spaces, many women become trapped in a vicious cycle by chasing gambling losses; this cycle increases their vulnerability to IPV [ 14 ]. International studies and those undertaken in Australia, report higher IPV victimisation rates amongst women with a gambling problem than men [ 4 , 5 , 15 ]. Not surprisingly, women experiencing both gambling harm and IPV often find themselves in very complex and challenging situations.…”
Section: Introductionmentioning
confidence: 99%
“…However, by using gambling venues as safe spaces, many women become trapped in a vicious cycle by chasing gambling losses; this cycle increases their vulnerability to IPV [ 14 ]. International studies and those undertaken in Australia, report higher IPV victimisation rates amongst women with a gambling problem than men [ 4 , 5 , 15 ]. Not surprisingly, women experiencing both gambling harm and IPV often find themselves in very complex and challenging situations.…”
Section: Introductionmentioning
confidence: 99%
“…One harm associated with gambling is domestic and family violence, with higher rates of perpetration and victimization found among individuals with a gambling problem ( Afifi et al, 2010 ; Dowling et al, 2018 ; Roberts et al, 2018 ). Intimate partners are most commonly the victims and perpetrators of this violence, although violence related to gambling also occurs amongst other family members ( Dowling et al, 2014 ; Bellringer et al, 2017 ; Palmer du Preez et al, 2018 ). Gambling research has sought to understand the prevalence of this violence, characteristics of perpetrators and victims, why this violence occurs, and how it is linked to gambling.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous international studies report higher IPV victimization rates among women with a gambling problem compared to men, although prevalence rates are inconsistent across studies (Bellringer et al, 2017; Dowling et al, 2014; Echeburúa et al, 2011; Lavis et al, 2015). According to Dowling et al (2014), 27% of gamblers attending gambling help services in Australia experienced physical violence; women experienced higher rates than men.…”
Section: Introductionmentioning
confidence: 99%
“…Research undertaken in other countries echoes these findings; in Spain, for example, Echeburúa et al (2011) found that women with a gambling problem were 10 times more likely to be a victim of current or recent IPV when compared to the overall rate for women in that country. In New Zealand, past-year IPV victimization rates were 57% for women with gambling problems (Bellringer et al, 2017). Although most studies’ measurement instruments do not illuminate the gendered context of violence, there is little doubt that problem gambling is positively associated with IPV victimization, especially for women.…”
Section: Introductionmentioning
confidence: 99%